1975
DOI: 10.1126/science.1188357
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Serum 1α,25-Dihydroxyvitamin D 3 by Calcium and Phosphate in the Rat

Abstract: A new radioreceptor assay was used to quantify changes in serum concentration of 1alpha,25-dihydroxyvitamin D3 in rats with low calcium or low phosphate diets. Low availability of either ion elicits a fivefold increase in the circulating concentration of 1alpha,25-dihydroxyvitamin D3. The enhancement of 1alpha,25-dihydroxyvitamin D3 concentration in response to calcium deficiency is dependent on the presence of the parathyroid or thyroid glands (or both), suggesting that this effect is mediated by parathyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
0
3

Year Published

1976
1976
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(109 citation statements)
references
References 18 publications
8
98
0
3
Order By: Relevance
“…Cholecalciferol is hydroxylated in two steps: the first hydroxylation occurs at the carbon at the 25 position in the liver, and the second hydroxylation takes place in the kidney at the level of the carbon at the 1 position (18) . An increase in the serum levels of 1,25(OH) 2 D 3 by a low-Ca 2þ diet has been shown in human subjects (19) , chicks (20) , ewes (21) and rats (22) , but not in hamsters (23) . On the contrary, dietary Ca 2þ restriction in the presence of constant vitamin D intake may cause depletion of 25-hydroxycholecalciferol, as shown in the plasma of rats as a consequence of high activity of the renal enzyme 25-OH-cholecalciferol 1-hydroxylase (CYP27B1), which catalyses the transformation of 25-hydroxyvitamin D 3 (25OHD 3 ) into 1,25(OH) 2 D 3 (24) .…”
Section: Introductionmentioning
confidence: 99%
“…Cholecalciferol is hydroxylated in two steps: the first hydroxylation occurs at the carbon at the 25 position in the liver, and the second hydroxylation takes place in the kidney at the level of the carbon at the 1 position (18) . An increase in the serum levels of 1,25(OH) 2 D 3 by a low-Ca 2þ diet has been shown in human subjects (19) , chicks (20) , ewes (21) and rats (22) , but not in hamsters (23) . On the contrary, dietary Ca 2þ restriction in the presence of constant vitamin D intake may cause depletion of 25-hydroxycholecalciferol, as shown in the plasma of rats as a consequence of high activity of the renal enzyme 25-OH-cholecalciferol 1-hydroxylase (CYP27B1), which catalyses the transformation of 25-hydroxyvitamin D 3 (25OHD 3 ) into 1,25(OH) 2 D 3 (24) .…”
Section: Introductionmentioning
confidence: 99%
“…Limitations of these earlier reports include 1) relatively insensitive and nonspecific methods of purification of 1,25(OH),D; 2) studies restricted to animals subjected to vitamin D-deficient diets; 3) use of media calcium concentrations in supraphysiologic millimolar ranges; and 4) inconsistencies in the methods and results among the various reports. For example, several studies demonstrated that Open columns, mitochondria incubated without calcium; hatched columns, mitochondria incubated with calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that the same relationships may exist in man comes from recent measurements of 1,25(OH)2CC in plasma which indicate that the levels are higher than normal in hyperparathyroidism and lower than normal in hypoparathyroidism (Hughes et al, 1975). They are also low in renal failure (Mawer et al, 1973) perhaps because renal mass is diminished or as a result of the hyperphosphaternia that exists in this condition.…”
Section: Regulation Of Calcium Metabolism 523mentioning
confidence: 92%
“…It is possible that the effects of vit D on bone mineralisation are secondary to changes in extracellular fluid concentrations of calcium and phosphate, but this explanation may be too simple to account for all the experimental and clinical observations. Unfortunately, there are no good experimental systems for studying skeletal mineralisation in vitro and the major effect of There is evidence that the effect of calcium deprivation in increasing 1,25(OH)2CC is mediated by increased secretion of PTH, whereas the effect of phosphate restriction is independent of PTH (Hughes et al, 1975).…”
Section: Regulation Of Calcium Metabolism 523mentioning
confidence: 99%